The Issue For Baitul Mal Managers in Promoting Muzakki Awareness Through Islamic Education - Ramli Ramli; Asmuni Asmuni; Lahmuddin Lubis (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
The Aceh Qanun and province and national governments have confirmed regulations for entities that manage zakat, infaq, waqf, and other assistance assets.This study examines Muzakki's zakat awareness. Muzakki has an obligation to hand up his assets in time and measure, but he either doesn't or gives them to the mustahik without consulting the Baitul Mal, resulting in a very low zakat collection.Qualitative research allows for clear and in-depth attainment of study objectives through theory application. This research relies on the official amil zakat institution, notably Baitul Mal Lhokseumawe administration.Baitul Mal Lhokseumawe promotes zakat muzakki through networking, collaboration, publication, and lectures. Communication develops.Now that people are more tech-savvy, all community activities are online, and most information is on social media like YouTube, Facebook, Instagram, and TikTok, Baitul Mal's challenge to raise awareness of muzakki in Lhokseumawe needs more attention. Mass media uses social media as the information funnel.In Lhokseumawe, muzakki know they must give zakat, but some prefer to give it to mustahik since it helps them immediately and they are well-known. Some muzakki give zakat outside Lhokseumawe to help family